2015
DOI: 10.1037/fam0000044
|View full text |Cite
|
Sign up to set email alerts
|

The interpersonal process model of demand/withdraw behavior.

Abstract: The demand/withdraw interaction pattern is a destructive cycle of relationship communication behavior that is associated with negative individual and relationship outcomes. Demand/withdraw behavior is thought to be strongly linked to partners' emotional reactions, but current theories are inconsistent with empirical findings. The current study proposes the interpersonal process model of demand/withdraw behavior, which includes linkages between each partners' emotional reactions and the interpersonal behavior o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 55 publications
4
39
0
2
Order By: Relevance
“…As emotional arousal increases, vocal folds open and close more rapidly, and f 0 increases (measured in Hertz (Hz)). F 0 as a measure of emotional arousal has also been shown to be meaningful in a range of studies on couples (e.g., Baucom et al, 2011;Baucom, Dickenson et al, 2015;Baucom, Sheng et al, 2015;Fischer et al, 2015Fischer et al, , 2017Weusthoff et al, 2013). F 0 as a measure of emotional arousal has also been shown to be meaningful in a range of studies on couples (e.g., Baucom et al, 2011;Baucom, Dickenson et al, 2015;Baucom, Sheng et al, 2015;Fischer et al, 2015Fischer et al, , 2017Weusthoff et al, 2013).…”
Section: Emotional Arousalmentioning
confidence: 98%
See 1 more Smart Citation
“…As emotional arousal increases, vocal folds open and close more rapidly, and f 0 increases (measured in Hertz (Hz)). F 0 as a measure of emotional arousal has also been shown to be meaningful in a range of studies on couples (e.g., Baucom et al, 2011;Baucom, Dickenson et al, 2015;Baucom, Sheng et al, 2015;Fischer et al, 2015Fischer et al, , 2017Weusthoff et al, 2013). F 0 as a measure of emotional arousal has also been shown to be meaningful in a range of studies on couples (e.g., Baucom et al, 2011;Baucom, Dickenson et al, 2015;Baucom, Sheng et al, 2015;Fischer et al, 2015Fischer et al, , 2017Weusthoff et al, 2013).…”
Section: Emotional Arousalmentioning
confidence: 98%
“…Fundamental frequency (perceived as pitch) has been shown to be meaningful in a variety of couple interaction studies focused either on average levels of arousal (e.g., Fischer et al, 2015;Weusthoff, Baucom, & Hahlweg, 2013) or within-conversation interpersonal processes (e.g., Baucom, Dickenson et al, 2015;Baucom, Sheng et al, 2015;Fischer et al, 2017). It is also well suited to examine continuous shifts throughout a conversation.…”
mentioning
confidence: 99%
“…From a methodological perspective, this study adds to a growing literature on vocally encoded emotional arousal in couples, although prior studies were not focused on couples in which one partner has a psychological disorder (Baucom, Dickenson, et al, 2015; Baucom, Weusthoff, et al, 2012; Fischer, Baucom, et al, 2015; Weusthoff et al, 2013). However, these studies collectively suggest that vocally encoded arousal plays an important role for our understanding of couple interactions in a variety of contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Broadly, several studies demonstrated that overall levels of f 0 (Baucom et al, 2011; Baucom, Weusthoff, Atkins, & Hahlweg, 2012; Fischer, Baucom, et al, 2015) as well as within-conversation changes (Baucom, Dickenson, et al, 2015; Baucom, Sheng, et al, 2015) are associated with cross-sectional and longitudinal relationship outcomes. Similarly, Weeks and colleagues (Weeks, Heimberg, & Heuer, 2011; Weeks et al, 2012) demonstrated meaningful associations between f 0 during social threat tasks and symptom severity/diagnosis of social anxiety disorder.…”
mentioning
confidence: 99%
“…This work has resulted in numerous algorithms for automatically measuring well-established behavioral markers of relationship distress during couple conversations about relationship problems [47] as well as discovery of behavioral and emotional processes associated with acute emotional distress during couple conversations and during soldier-therapist interactions [48,49]. For example, one particularly important indicator of acute distress is the degree to which one person is emotionally responsive to the other.…”
Section: Relationship Conflict Behavior Behavioral Signal Processmentioning
confidence: 99%